Factors Affect Successful Fast-track Total Knee Arthroplasty - Tanavalee, MD, Chotetawan; Ngarmukos, MD, Srihatach; Wilairatana, MD, Vajara (Journal of Southeast Asian Orthopaedics, 2022)
Fast-track total knee arthroplasty (TKA) has been reported to improve patient’s clinical outcome, and decrease cost of treatment related to hospital stay. However, some drawbacks of early patient’s discharge have been reported, which caused surgeons to hesitate whether or not to apply the fast-track protocol in their practices. Literature has shown that besides patient’s factor which a decent patient selection played key role for successful fast-track TKA, other factors, including anesthesia factors and surgical factor, could facilitate the consistency of clinical outcome. The purpose of this review was to update and to determine factors which affected the fast-track protocol.